President Director Age, MBA Degree, and Earnings Management - Siska Rohaliza; Emrinaldi Nur DP; Poppy Nurmayanti M (Indonesian Journal of Economics, Social, and Humanities, 2022)
This study aimed to examine the effect of president director’s characteristics (i.e., age and MBA degree) on earnings management. This study used accrual earnings management with abnormal accruals as a proxy and real activity earnings management with abnormal discretionary expense as a proxy for earnings management. The population is all manufacturing companies listed on the Indonesia Stock Exchange between 2016 and 2019. The sample was selected based on the purposive sampling method, so that the companies sampled were 91 companies with a total of 364 observations. The data analysis method used is multiple regression analysis. These results find that age has a negatively significant effect on abnormal accruals and has not significant effect on abnormal discretionary expense. An MBA degree as a proxy for education has a positively significant effect on earnings management. Our results are consistent with the predictions of the upper echelons theory and have implications for various stakeholders, as well as providing insight for regulators in determining the qualifications or requirements to become president director